Pearls from the 2024 European Respiratory Congress (Actualité en allergologie et en immunologie au Canada, 2024)
The European Respiratory Congress 2024, held from September 7th to 11th, 2024, in Vienna, Austria, featured several presentations on airway diseases, interstitial lung diseases, bronchiectasis, and critical care, with a focus on emerging therapies, particularly on asthma and chronic obstructive pulmonary disease (COPD).